2015
DOI: 10.1063/1.4919923
|View full text |Cite
|
Sign up to set email alerts
|

Graphite edge controlled registration of monolayer MoS2 crystal orientation

Abstract: Transition metal dichalcogenides such as the semiconductor MoS2 are a class of two-dimensional crystals. The surface morphology and quality of MoS2 grown by chemical vapor deposition are examined using atomic force and scanning tunneling microscopy techniques. By analyzing the moiré patterns from several triangular MoS2 islands, we find that there exist at least five different superstructures and that the relative rotational angles between the MoS2 adlayer and graphite substrate lattices are typically less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
(14 reference statements)
7
33
0
Order By: Relevance
“…Atomic resolution STM image taken on the substrate is shown in Fig. 2(c) where the lattice constant is determined to be 2.46 ± 0.02 Å in good agreement with the lattice parameter of HOPG3136. Figure 2(d) shows an atomic resolution image acquired on monolayer MoS 2 where the lattice constant is 3.13 ± 0.03 Å, in agreement with literature values3136.…”
Section: Resultssupporting
confidence: 83%
“…Atomic resolution STM image taken on the substrate is shown in Fig. 2(c) where the lattice constant is determined to be 2.46 ± 0.02 Å in good agreement with the lattice parameter of HOPG3136. Figure 2(d) shows an atomic resolution image acquired on monolayer MoS 2 where the lattice constant is 3.13 ± 0.03 Å, in agreement with literature values3136.…”
Section: Resultssupporting
confidence: 83%
“…This case is rare since the rotational angles of CVD grown MoS 2 on HOPG, tend to be small. [23][24][25][26] The corresponding ball model is drawn in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%
“…40 In our experience, the underlying HOPG substrate can be imaged directly, by using an atypically large set-point current of 50 nA. 24 Thus, not only the surface's information, but also that of the underlying layer can be detected using STM. 31 On the other hand, first-principles investigations have revealed that there may be a weak but clear charge redistribution in the space between MoS 2 and graphene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations